2021
DOI: 10.3390/ani11061759
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Perineural Femoral Nerve Injection in Pigs Using an Ultrasound-Guided Lateral Subiliac Approach—A Cadaveric Study

Abstract: Desensitizing the femoral nerve (FN) improves pain control in several species undergoing pelvic limb surgeries. Despite its advantages, this method has not yet been described in pigs, although they make an accepted surgical animal model. Based on anatomical dissections, first performed in two pig cadavers, an ultrasound-guided access for localization and perineural infiltration of the FN trunk at the iliopsoas compartment level was specified. The FN was found running between the psoas major and medial portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The porcine model has been an accepted translational model for humans for decades [28], but even though the transcutaneous approach is the most used in humans [15], only laparoscopic [12] and endoscopic ultrasound-guided [13,14] techniques to block the CP have been described in experimental settings in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The porcine model has been an accepted translational model for humans for decades [28], but even though the transcutaneous approach is the most used in humans [15], only laparoscopic [12] and endoscopic ultrasound-guided [13,14] techniques to block the CP have been described in experimental settings in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The femoral-sciatic nerve block is a regional anaesthetic technique well described in small and farm animals. 7,[46][47][48][49][50] At present, few case reports have described this locoregional technique in different avian species: d'Ovidio et al described a nerve stimulator-guided femoral-sciatic nerve block in raptors undergoing surgical treatment of pododermatitis, while Trujanovic et al reported the same block in a duck undergoing surgical fixation of a tibiotarsal fracture guided by both ultrasound and nerve stimulator. In the present case, due to the small size of the animal, the ultrasonography visualisation of the femoral nerve was challenging, hence the decision of using the nerve stimulator.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we opted for a multimodal analgesic approach, which included the use of an opioid in premedication, as discussed above, combined with a local anaesthetic technique and ketamine infusion. The femoral‐sciatic nerve block is a regional anaesthetic technique well described in small and farm animals 7,46–50 . At present, few case reports have described this locoregional technique in different avian species: d'Ovidio et al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of locoregional anaesthesia techniques for various surgical procedures, now commonplace in dogs and cats, has been reported in other species, including sheep [6], calves [7], goats [8,9], and pigs [10,11]. Local nerve blocks may be performed blind or guided by electrical nerve stimulation or ultrasound.…”
Section: Introductionmentioning
confidence: 99%